(untitled) (Archives of Criminology, 2002)
The past fifteen years or so have been a time of significant changes in Polish religious life. The most notable feature has been a growth in the significance of the native religion which for the overwhelming vast majority of Poles is Catholicism. According to official statistics members of the Catholic Church in Poland constitute 95% of the population, other Christian faiths account for just under 3% and adherents of other religions, sects, religious and pseudo-religious or world view-based movements, including atheism, for only about 2%. However, another phenomenon has been taking place in the shadow of the process of change: the appearance and spread of new religious and para-religious movements. In Poland these movements appeared at a somewhat later date than in the West where their first wave of popularity coincided with the rise of the youth counter-culture movement at the turn of the sixties and seventies. New religious movements began to appear in Poland in the seventies and eighties and have become a permanent feature of the religious landscape though, statistically, they are still a marginal phenomenon compared with Catholicism. The proliferation of sects or cults of every kind and description is one of the more remarkable and individual-threatening phenomena of the turn of the 20th and 21st centuries. Each year about 12,000 young Poles run away from home or disappear. Many of them discover “the sole truth” in one of the 300 new religious movements to be found in Poland. But that assertion does not justify drawing the erroneous conclusion that all these young people swell the ranks of religious sects though undoubtedly a certain, unknown, number of them end up in such organizations. The author has conducted a survey among students of primary and secondary schools, in the sity of Białystok and the law department of the local university. The aim of the investigation, carried out by the questionnaire method, was to elicit information about young people’s awareness of the religious sects phenomenon and test the accuracy of the project’s theoretical hypotheses. The survey’s findings are presented in this publication separately for each age group of respondents: students of the eighth school grade of primary school and the last year of secondary school and uno undergraduates. Also included was a comparative analysis of the findings according to the age of the subjects, which was the basic variabre considered when preparing the report. The publication ends with a tabular section which serves the purpose of detailed presentation of the respondents’ answers to question regarding the sources of their knowledge of religious sects, the range of persons thought by the respondents to form the recruitment pool for converts to religious sects, and social distance. This section also contains the questionnaire used in the survey. The author undertook her research endeavor in the belief that beyond any doubt the population group most at risk from the activities of religious sects is youth. Thus there were good grounds for investigation or this social group in order to determine its level of awareness of religious sects and emotional attitude to them. As well as diagnosis of the phenomenon such an operation facilitates attempts to devise an information policy targeted young people. The investigation, which took the form of interviews, used a questionnaire designed for this purpose. The survey was carried out in the first quarter of 1999 among students of primary and secondary schools in Białystok and the law department of the local university. The sample analyzed in the study comprised 100 students of the eighth grade of primiry school, l00 high school seniors and 100 undergrauates. The breakdown in the eighth-graders subgroup was 48% female and 52% male. The respective proportions for the high school seniors were 30% and 70% and for the college students 45% and 55%. The 300-person youth sample so selected is a fair representation and allows for certain inferences to be made to the wider population. The respondents were informed of the subject and aim of the investigation, the method of completing the questionnaire and its anonymity. The empirical material gathered was characterized by a relatively small amount of incomplete data. Such instances were of a sporadic and random nature. The investigation aimed at testing basic hypotheses. Based on analysis of the literature and the findings of earlier empirical studies five specific working hypotheses were adopted: Young people’s basic source of information about religious sects is the mass media. Young people are not tolerant about admitting members of religious sects to their immediate social circle, while the degree of tolerance does not depend on age. Young people are aware that thy constitute the group most vulnerable to the activities of religious sects. Awareness of the dangers posed by sects increases with the age of the respondent. Awareness of the dangers posed by sects increases in step with advancement to the next step of the education ladder. The level of awareness of youth as regards the religious sects phenomenon and the dangers arising there from was strictly correlated with the age of the subjects and consequently also by their standard of education. The make-up of the different components of young people’s attitudes to sects varied according to the age bracket of the respondents. As regards familiarity with the religious sects phenomenon it was found to be universal and irrespective of whether the respondent was an eighth-grader, high school senior or college student. However, certain differences appeared in the kinds of sources from which the young derive their knowledge of sects. Analysis of the findings corroborated the hypothesis that youth is aware of the fact that it is the group most vulnerable to the activities of sects. Though none of the sample gave a full definition of sect it is satisfying to note that every one of the respondents identified correctly at least one of the basic characteristics, e.g. a distinctive ideology and practices, resort to subterfuge and lies in recruitment of new members, or the exceptional position of the guru. Interestingly, a decided majority in each of the groups surveyed perceived the negative phenomenon of sects. Generally speaking, college students as persons with ihe highest level of awareness of the dangers posed by sects assessed them unfavorably, though they were not as radical in their assessments as the eighth-graders or high school seniors. The most opposition in all the age groups studied was aroused by the idea of admitting a sect member into the family circle, the least by the possibility of having a sect adherent for a colleague. Analysis of replies to questions relating to social distance leads to the conclusion that the young people studied were not indifferent to the henomenon of religious sects. Sect members were not approved of in high public office. They were not well thought of in the role of schoolteachers or adoptive parents. Almost all of the college students and high school seniors in the survey expressed a belief that some religious sects were breeding grounds of crime. A decided majority of the eighth-graders and high school seniors thought that the functioning of sects ought to be prohibited by law. As regards the respondents’ views on the question of whether registration of religious sects should be made easier or harder there were also certain variations according to respondents’ age. Among the college students and high school seniors a decided majority were in favor of impeding registration of religious sects in Poland. By contrast, in the case of the primary school eighth graders such a belief was expressed by 49% while 43% had no opinion on the subject. This is perhaps to be explained by the fact that the latter do not posses the knowledge required to form an opinion on this matter.